Improving biodiversity literacy through flipped classroom assisted by pteridophyte identification worksheets in Masigit Kareumbi - Siti Humairoh; Mar'atus Sholikha; Epa Paujiah; Fadli Emsa Zamani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: The limited allocation of face-to-face time and the high prevalence of plant blindness lead to plant world learning that tends to be theoretical and memorization-oriented, thereby contributing to students' low biodiversity literacy. Objectives: This study aims to analyze the effect of applying the Flipped Classroom model, assisted by worksheet identification of Pteridophyte, on students' biodiversity literacy skills in the Mount Masigit Kareumbi area. Methods: A quasi-experimental non-equivalent control group design involved 70 students, selected through cluster random sampling and divided into experimental (n = 35) and control (n = 35) classes. The intervention was conducted in two sessions, each lasting three lessons. Data were collected using written tests, observations, and questionnaires, then analyzed using N-Gain and independent-samples t-tests. Both groups showed equivalent baseline performance, with an identical mean pretest score of 37.0. Results: The results showed that the experimental class obtained an average posttest score of 62.9, with an N-Gain of 0,51 (medium), higher than the control class, which had a posttest score of 50.9 and an N-Gain of 0,28 (low). The difference was statistically significant (p = 0.019), with a Cohen’s d value of 0.392, indicating a medium effect size. Student responses to the learning process were very good, with an average of 93.9%. Conclusions: Thus, implementing the Flipped Classroom model, supported by student worksheets tailored to local potential, effectively increased students' biodiversity literacy and ecological awareness. This study provides a practical guide for utilizing local conservation resources as active biology learning tools.